Origin of domesticated water chestnuts (Trapa bispinosa Roxb.) and genetic variation in wild water chestnuts - Dinh Thi Lam; Taro Kataoka; Hiroki Yamagishi; Guoping Sun; Tetsuro Udatsu; Katsunori Tanaka; Ryuji Ishikawa (Ecology and Evolution, 2024)
Abstract The water chestnut Trapa bispinosa Roxb. has been domesticated in China and has been reported as the only domesticated species of this genus. To understand the origin of T. bispinosa and its evolution pathway, we compared the genetic similarity and seed morphology of domesticated water chestnut T. bispinosa with three wild species T. natans, T. incisa, and T. japonica along with archeological seed samples from the Tianluoshan site (approximately 7000–6300 cal BP) in China. The largest seed size was observed only in the domesticated species, whereas other wild species showed smaller size including T. natans L. genetically close to the domesticated type, and T. incisa was the smallest in size. The volumes of the seed capsule and endosperm were measured using X ray CT scans, showing the ratios of total volumes between T. bispinosa and wild species ranged from 4.2 to 4.5. The ratios of endosperm volume ranged from 3.3 to 3.7. Both measurements showed domesticated species have larger seed volume. Genome size was indirectly estimated by flow cytometry. Domesticated species with larger seed size was estimated as diploid, as were the wild species except for tetraploid species T. japonica. Domesticated species clearly showed the largest edible organs, but it was not a result of ploidy level changes. Maternal lineages traced using complete whole chloroplast sequences, suggested that T. natans is the closest to T. bispinosa, both of which are close to T. japonica. The result was confirmed by PCR genotyping with chloroplast insertion/deletion (cpINDEL) markers developed in the study. T. incisa showed distinct plastid types within the species, and T. japonica showed a unique plastid genotype. Our study concludes the largest volumes for the edible endosperm have been accomplished through nearly 6000 years of artificial selection, but the domestication did not involve ploidy level changes.